2006
DOI: 10.1590/s0100-879x2006001200016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute exposure to air pollution on the cardiorespiratory performance of military firemen

Abstract: The objective of the present study was to determine the impact of acute short-term exposure to air pollution on the cardiorespiratory performance of military fireman living and working in the city of Guarujá, São Paulo, Brazil. Twenty-five healthy non-smoking firemen aged 24 to 45 years had about 1 h of exposure to low and high levels of air pollution. The tests consisted of two phases: phase A, in Bertioga, a town with low levels of air pollution, and phase B, in Cubatão, a polluted town, with a 7-day interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the aforementioned study by Oliveira et al (2006), firefighters performed exertion tests in low and high air pollution ambient environments and found no differences in maximal performance, but did observe decreased submaximal performance in the high pollution environment. The authors suggested that the results were due to diminished oxygen transport resulting from increased levels of carboxyhemoglobin (COHb), though CO levels were not provided.…”
Section: Performancementioning
confidence: 89%
See 1 more Smart Citation
“…In the aforementioned study by Oliveira et al (2006), firefighters performed exertion tests in low and high air pollution ambient environments and found no differences in maximal performance, but did observe decreased submaximal performance in the high pollution environment. The authors suggested that the results were due to diminished oxygen transport resulting from increased levels of carboxyhemoglobin (COHb), though CO levels were not provided.…”
Section: Performancementioning
confidence: 89%
“…For instance, the 1 st and 11 th place finishers in the 3000 m steeplechase at the 2008 Olympics, an event similar in duration to the maximal exercise bouts used in the present study, were separated by less than 2.87%. Submaximal performance has also been shown to be decreased after HPM exposure (Oliveira et al, 2006), therefore, we suspect that aerobic events of greater duration which rely heavily on aerobic metabolism are most likely affected by changes in the pulmonary and systemic vasculature. Marr and Ely (2010) found that PM 10 was associated with impaired marathon performance for women but not men.…”
Section: Performancementioning
confidence: 98%
“…Controlled particulate pollution exposures during exercise tests have shown to reduce workload among small studies enrolling young men 11. In healthy young individuals, lower VT18 and VO 2peak 12 have been observed while exercising in locations with higher pollution. Particulate exposure during or before exercise has been associated with ST-segment changes,19 autonomic imbalance20 and increased exercise BP21 in cardiac patients; however, we are not aware of any prior study of directly measured aerobic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…(19,20) In addition, deployment in areas with high levels of air pollution at baseline can also impair the cardiorespiratory performance of personnel. (21) While respiratory protection can be achieved via engineering and administrative controls, this may not always be possible. Thus, the usage of appropriate FFRs as PPE is important to protect personnel from the effects of particulates, either from occupational exposure or due to deployment to areas with significant air pollution.…”
Section: Discussionmentioning
confidence: 99%